أثر استقلالية مجلس الإدارة في دعم الإفصاح المحاسبي عن معلومات الاستدامة وانعكاسها في الأداء المالي: دراسة تجريبية باستخدام تحليل مغلف البيانات - حسين، علي إبراهيم; سمير، أحمد زياد (جامعة تكريت - كلية الإدارة والاقتصاد, 2020)
The research aims to test the effect of the independence of the Board of Directors in disclosing sustainability information and its reflection on the financial performance of banks listed on the Iraq Stock Exchange for the period from 2014 to 2018. The research addressed a method of content analysis of the annual financial lists of the 12 banks. Using the models regression simple and correlation add to method of Data Envelopment Analysis DEA. The study concluded that there is a significant relationship and impact of the Board’s independence in supporting the disclosure of sustainability information and financial performance, and the study also found a positive impact of the disclosure of sustainability information on the financial performance. And that the impact of the board independence of directors on financial performance increases when mediating the disclosure of sustainability information.
يهدف البحث إلى اختبار تأثير استقلالية مجلس الإدارة في الإفصاح عن معلومات الاستدامة وانعكاسها في الأداء المالي في المصارف المدرجة في سوق العراق للأوراق المالية وللفترة الممتدة من ٢٠١٤ وإلى عام ٢٠١٨، تناول البحث أسلوب تحليل محتوى للقوائم المالية السنوية للمصارف البالغ عددها ١٢ مصرفا، وباستخدام نموذج الانحدار والارتباط البسيط وأسلوب تحليل مغلف البيانات. وقد أشارت النتائج إلى وجود علاقة وتأثير ذو دلالة معنوية لاستقلالية المجلس في دعم الإفصاح عن معلومات الاستدامة والأداء المالي، وكذلك تشير النتائج إلى وجود تأثير إيجابي للإفصاح عن معلومات الاستدامة في الأداء المالي وإن تأثير استقلالية مجلس الإدارة في الأداء المالي يزداد عند توسيط الإفصاح عن معلومات الاستدامة.
Keywords: التنمية المستدامة -- الإفصاح المحاسبي -- الأداء المالي -- الاقتصاد العراقي